The Role of Bekasi City Government in Overcoming Pollution of Bekasi River 2023 - Muhamad Alvi; Kusuma, Ardli Johan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The Bekasi river water pollution issue, which had actually occurred in 2016, finally broke out again in 2023 and had an impact on the PDAM's raw water source which will be managed into clean water to be distributed to the community. In the process, there was a conflict between the Bekasi City Environment Agency and the Bogor Regency Environment Agency, related to the source of the problem and the handling of watershed pollution. This research aims to find out more about the role of the Bekasi City Government in overcoming the impact of clean water pollution for the people of Bekasi, in 2023. Sourced from interviews and secondary sources in the form of journals, this research uses a case study method. Data was collected in Bekasi city and Bogor district, in 2023 and expanded in 2024. The results state that there is collaboration between the Bekasi City Government and the Bogor Regency Government to deal with the problem of clean water pollution in the Bekasi River sub-watershed. The Bekasi City Government and Bogor Regency Government have conducted monitoring, guidance, supervision, and control on wastewater licensing. The Bogor district government has also taken action against 26 rogue companies proven to be discharging waste into the watershed. However, the community believes that they have not felt the real results of the efforts made by the government, because Kali Bekasi is still polluted during the dry season.